2021
DOI: 10.34117/bjdv7n9-121
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Spirulina platensis in handmade ice cream: Phisicochemical and sensory effects / Adição de Spirulina platensis em sorvete caseiro: Efeitos físico-químicos e sensoriais

Abstract: Spirulina microalgae possess proven benefits to health. It presents antioxidants that needs to be protected during the food processes, what can be done using microencapsulation techniques. Besides, the encapsulation could prevent the rejection of the food added of Spirulina due to the seaweed flavor. The aim was to accomplish the microencapsulation of Spirulina in maltodextrin and Arabic gum and evaluate the influence in the physicochemical and sensorial profile of handmade ice cream. The ice cream with Spirul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Paternina et al [ 66 ] found that gummy candies with Spirulina at concentrations of 1, 3, and 5% received scores for overall acceptability between 7.09 and 7.22. In the study of Tiepo et al [ 65 ], the overall impression of ice cream with Spirulina was lower than the control ice cream. According to Lucas et al [ 67 ], the overall acceptance of extruded snacks with Spirulina was expressed as “like moderately” and “like very much”.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Paternina et al [ 66 ] found that gummy candies with Spirulina at concentrations of 1, 3, and 5% received scores for overall acceptability between 7.09 and 7.22. In the study of Tiepo et al [ 65 ], the overall impression of ice cream with Spirulina was lower than the control ice cream. According to Lucas et al [ 67 ], the overall acceptance of extruded snacks with Spirulina was expressed as “like moderately” and “like very much”.…”
Section: Resultsmentioning
confidence: 98%
“…Incorporation of microalgae in foods can lead to various forms of sensory acceptability due to the different processing and balance of the ingredients. Because of changes in colour, flavour, and texture, product acceptability can be reduced when microalgae concentration rises [ 65 ]. Paternina et al [ 66 ] found that gummy candies with Spirulina at concentrations of 1, 3, and 5% received scores for overall acceptability between 7.09 and 7.22.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Matos et al (2021) prepared yoghurt enriched with freeze-dried biomass of Isochrysis galbana and observed an increase of about 25% in the PC. Tiepo et al (2021) also formulated ice cream with Spirulina and observed that the PC was increased by 53% as compared to the control. Likewise, Bosnea et al (2020) incorporated 1% Spirulina platensis in the production of soft cheese and observed an increase of 9.80% in the PC of the prepared cheese.…”
Section: Dairy Industrymentioning
confidence: 99%
“…Tiepo et al . (2021) also formulated ice cream with Spirulina and observed that the PC was increased by 53% as compared to the control. Likewise, Bosnea et al .…”
Section: Application Of Algal Protein In Food Industrymentioning
confidence: 99%
“…Spirulina has been employed in the transformation of various conventional food items, including the incorporation of Spirulina into cookies, pasta, and ice cream, and its blending with juices, such as its combination with pomegranate juice [7]- [9]. The analysis of industrial and market trends indicates that the Spirulina-based dietary supplement market is at the forefront, and it is projected that by the year 2031, the market is poised to reach a value of $254 billion, experiencing a Compound Annual Growth Rate (CAGR) of 9.4% [10].…”
Section: Introductionmentioning
confidence: 99%